2000
DOI: 10.1016/s0002-9440(10)64639-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Resolution of Light Chain-Associated Amyloid Deposits

Abstract: Primary light-chain-associated (AL) amyloidosis is characterized by the deposition in tissue of monoclonal light chains as fibrils. With rare exception, this process is seemingly irreversible and results in progressive organ dysfunction and eventually death. To determine whether immune factors can effect amyloid removal, we developed an experimental model in which mice were injected with amyloid proteins extracted from the spleens or livers of patients with AL amyloidosis. Notably, the resultant amyloidomas we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(139 citation statements)
references
References 39 publications
4
134
0
1
Order By: Relevance
“…These antibodies do not, however, bind to the soluble precursors of these fibrils, nor do they bind to other forms of protein aggregates such as bovine collagen, elastin or gelatin. In addition, a monoclonal antibody raised against amyloid proteins extracted from spleens and livers of patients with immunoglobulin light chain-associated amyloidosis, has been reported to recognise ex vivo amyloid fibrils composed of the light chain variable domain, Ab, and other amyloidogenic proteins [71].…”
Section: Probes Of Structural Features Of Mature Fibrilsmentioning
confidence: 99%
See 2 more Smart Citations
“…These antibodies do not, however, bind to the soluble precursors of these fibrils, nor do they bind to other forms of protein aggregates such as bovine collagen, elastin or gelatin. In addition, a monoclonal antibody raised against amyloid proteins extracted from spleens and livers of patients with immunoglobulin light chain-associated amyloidosis, has been reported to recognise ex vivo amyloid fibrils composed of the light chain variable domain, Ab, and other amyloidogenic proteins [71].…”
Section: Probes Of Structural Features Of Mature Fibrilsmentioning
confidence: 99%
“…If a similar phenomenon is observed in humans, such an antibody may be useful for quantifying brain amyloid burden in patients who have been diagnosed with Alzheimer's disease, or even known to be at risk of developing it. Finally, antibodies that bind to the generic epitope(s) of oligomeric aggregates or fibrils such as those described above [61,70,71], may prove to be reagents able to diagnose the whole family of amyloid diseases.…”
Section: Diagnostic Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we had previously reported that the IgG1 mAb 11-1F4, generated by immunizing mice with a thermally denatured variable region fragment of the human Igκ4 Bence Jones protein Len, reacted specifically with light chain (LC) fibrils, irrespective of κ or λ isotype but, notably, did not with native molecules (Hrncic, R. et al (2000) Am. J. Pathol.…”
mentioning
confidence: 99%
“…The process then can be accelerated by passive administration of an apparently conformation specific antibody. 93,94 In contrast to the systemic amyloidoses, it has been well recognized that glial activation is common, if not universal, in the neighborhood of Ab plaques in the Alzheimers Disease brain. 95 It has been experimentally shown that Ab fibrils can activate glia and this may be mediated by the nuclear factor kappa B pathway triggered via RAGE or CD36.…”
Section: Interfaces Between the Amyloidoses And The Immune Systemmentioning
confidence: 99%